Impact of change in promoters' shareholding pattern on the performance of small-cap-value equity stocks in the national stock exchange of India - Ritesh Ashok Khatwani; Gopala Raghuram; Mahima Mishra; Janki Mistry (Journal of Risk and Financial Management, 2023)
This paper studies the impact of a change in promoter shareholding on small-cap-value stocks. NIFTY Small Cap 250 index stocks within the top 20th percentile of the book-to-market (B/M) ratio of the same universe have been considered for this study. The paper uses regression analysis for understanding the impact of independent variables on returns. The universe is further narrowed down to stocks with a positive change in promoter shareholding, which is found to be negatively related to stock returns. In addition, although the book-to-market ratio does not play any role in the prediction of returns while within this narrowed-down universe, the size effect is present. The results are discussed with reference to some relevant past research literature, and the scope for further research is also discussed.
Keywords: 650; book-to-market ratio; G-score; NSE; promoter; shareholding; small cap